1998
DOI: 10.1007/s003290050073
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial cavernous malformations — natural history and management

Abstract: Thirteen papers on different aspects of cerebral cavernomas are reviewed; interest in this condition has increased since magnetic resonance imaging (MRI) became widely available. The prevalence of cavernomas is uncertain, but they are the most common of the angiographically occult vascular malformations. Some are isolated occurrences, and some are familial, with a dominant inheritance. Screening with MRI of first-degree relatives is justified. The reported annual risk of haemorrhage varies widely and is probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Of patients who harbor a single CCM, undergo lesionectomy for treatment of recent-onset, localization-related seizures, and are seizure free postoperatively, up to half may successfully taper off all anticonvulsant medications. 21,35,64,69 This promising outcome, and its associated positive impact on quality of life, may play a role in the decision to excise a solitary accessible cortical CCM, even when seizures are not truly intractable to medical therapy.…”
Section: Lesion Excisionmentioning
confidence: 99%
“…Of patients who harbor a single CCM, undergo lesionectomy for treatment of recent-onset, localization-related seizures, and are seizure free postoperatively, up to half may successfully taper off all anticonvulsant medications. 21,35,64,69 This promising outcome, and its associated positive impact on quality of life, may play a role in the decision to excise a solitary accessible cortical CCM, even when seizures are not truly intractable to medical therapy.…”
Section: Lesion Excisionmentioning
confidence: 99%
“…11,39,51,52 In most series, however, an equal distribution between the sexes 13,24,26,31,40,43,48,53 has been reported, and this was also the case in ours. Some authors have suggested a higher propensity for bleeding episodes in female patients, 16,48 often during pregnancy. 45 There has also been a report of sudden death in a pregnant patient, in whom a cerebellar CM was diagnosed at autopsy.…”
Section: Age and Sex Of The Patientsmentioning
confidence: 99%
“…For those who have suffered previous bleeding, the annual risk increases to 4.3% per patient. 16 In those harboring posterior fossa CMs and those who have experienced a previous hemorrhage it is 6.75 and 7.78 times more likely, respectively, that they will present with neurological sequelae. 39, 45 Cantu, et al, 10 reported that the risk of intracerebral hemorrhage was only 1.22% per patient per year in lobar CMs and 2.33, 2.39, and 2.82% per patient per year for brainstem, cerebellum, and deep hemispheric CMs, respectively.…”
Section: Treatment Optionsmentioning
confidence: 99%
See 2 more Smart Citations